DLTS characterization of defects in GaN induced by electron beam exposure. (15th June 2017) - Ngoepe, P.N.M.; Meyer, W.E.; Auret, F.D.; Omotoso, E.; Diale, M.
Abstract: The deep level transient spectroscopy (DLTS) technique was used to investigate the effects of electron beam exposure (EBE) on n -GaN. A defect with activation energy of 0.12 eV and capture cross section of 8.0×10 –16  cm 2 was induced by the exposure. The defect was similar to defects induced by other irradiation techniques such as proton, electron, and gamma irradiation. In comparison to GaN, the EBE induced defects in other materials such as Si and SiC are similar to those induced by other irradiation methods.